Inclusivity and Accessibility of RTI Act in Bangladesh How do women in Rangpur Division view their access to information? - Mashrafy, Moonmoon (The Jahangirnagar Review, 2024)
The RTI Act provides the legal means to obtain the power that comes with information. It is necessary to practise and execute the Act in order to exercise the right to information. The involvement of women in the process is less advanced than that of males. Drawing a scenario of women’s engagement is the primary goal of the current study. Finding the problems and coming up with remedies at the field level are the two additional objectives. Throughout the objectives, the study responds to one main question and two related ones. This study based on mixed contained research inquiry pertains to the state of women’s involvement in the implementation of the RTI Act. It is revealed from the study that Information Commission does not provide information specifically targeted at women, despite their lack of strong endorsement about women’s engagement in relation to the RTA’s efficacy criteria. most women do not know about the RTI Act. Though women’s backwardness is mainly due to their illiteracy, other factors like economic dependency, bullying, family, patriarchic society, religion, culture, and the scariness of law are also responsible for women’s backwardness. Women’s apathetic attitude is one the major causes of women’s backwardness to the implementation process of the RTI Act. Indifferences of Institutions and the lack of a friendly environment are also responsible for women’s backwardness. However, a small number of women know they are interested in applying for many reasons. The study mentions that different types of campaigns are fundamental to spreading knowledge and enhancing women’s consciousness about the RTI Act.